Improving the Quality of Learning in Primary Schools - Ernawati, Ernawati; Harapan, Edi; Kesumawati, Nila (Yayasan Sembilan Pemuda Indonesia, 2021)
The purpose of this study is to identify school principals improves the quality of primary schools. The study was conducted at SD Negeri 1 Banyuasin III. The research was qualitative. The subject of the research is teachers in SD Negeri 1 Banyuasin III. Data were collected by interviews and analyzed using triangulation. The result showed that not all teachers can perform the task in full because obstacles covid 19, the solution applied is maximizing available resources.